Analytical Performances of the Panther Fusion System for the Detection of Respiratory Viruses in the French National Reference Centre of Lyon, France - Pichon, Maxime (Microorganisms, 2020)
Respiratory infection are mainly caused by viral pathogens. During the 2017–2018 epidemic season, Panther Fusion(®) Respiratory kits (Influenza virus A&B (FluA&B), respiratory syncytial virus (RSV), adenovirus (ADV), metapneumovirus (MPV), rhinovirus (RV), parainfluenzae virus (PIV), were compared to the Respiratory MultiWells System r-gene. Respiratory clinical specimens were tested retrospectively (n = 268) and prospectively (n = 463). Analytical performances were determined (sensitivity –Sep-, specificity –Spe- and κ) considering concordances of ≥2 molecular testing specific to each viral target (discrepant results were verified at the National Reference Centres for Enteroviruses or Respiratory viruses, Lyon, France). After retrospective (and prospective) testing, Sep, Spe, and κ were 100% (97.7%), 100% (99%) and 100% (94%) for FluA: 100% (95.5%), 100% (99.3%) and 100% (94%) for FluB, and 100% (88.5%), 100% (98.7%) and 100% (89%) for RSV; 82.1% (41.7%), 100% (99.5%) and 86% (54%) for ADV; 94.7% (73.7%), 96.1% (98.0%) and 91% (65%) for MPV; 96.1% (94.6%), 90.2% (98.5%) and 86% (91%) for HRV; and 90% (72.7%), 100% (99.3%) and 91% (72%), respectively, for PIV. Analytical performances were above 85% for all viruses except for ADV, MPV and PIV, confirming the analytical performance of the Panther Fusion system, a high throughput system with reduced turn-around-time, when compared to non-automated systems.